2003
DOI: 10.1002/ab.10076
|View full text |Cite
|
Sign up to set email alerts
|

Perpetrators of alcohol‐involved sexual assaults: How do they differ from other sexual assault perpetrators and nonperpetrators?

Abstract: Approximately 50% of sexual assaults involve alcohol. Researchers have documented situational characteristics that distinguish between sexual assaults that do and do not involve alcohol, but little attention has been paid to differences between the perpetrators of these two types of assault. In this study, discriminant function analysis was used to distinguish between college men (N = 356) who reported perpetrating sexual assault that involved alcohol, sexual assault that did not involve alcohol, or no sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
123
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 53 publications
6
123
0
1
Order By: Relevance
“…Approximately half of all sexual assaults are associated with alcohol consumption [Ageton, 1983;Muehlenhard and Linton, 1987;Seto and Barbaree, 1997;Tyler et al, 1998;Zawacki et al, 2003]. Men who are heavy drinkers or who report having alcohol problems are more likely than other men to have committed sexual assault [Abracen et al, 2000;Johnson and Knight, 2000;Merrill et al, 2001;Ullman et al, 1999].…”
Section: Theoretical and Empirical Research Identifying Predictors Ofmentioning
confidence: 99%
“…Approximately half of all sexual assaults are associated with alcohol consumption [Ageton, 1983;Muehlenhard and Linton, 1987;Seto and Barbaree, 1997;Tyler et al, 1998;Zawacki et al, 2003]. Men who are heavy drinkers or who report having alcohol problems are more likely than other men to have committed sexual assault [Abracen et al, 2000;Johnson and Knight, 2000;Merrill et al, 2001;Ullman et al, 1999].…”
Section: Theoretical and Empirical Research Identifying Predictors Ofmentioning
confidence: 99%
“…Many of these address gender-related attitudes and cognitions. For example, some research has shown an association between responses to rape-myth acceptance scales (e.g., "When women talk and act sexy, they are inviting rape"), which address misperceived justification of rape and of sexual assault perpetration (Carr and VanDeusen, 2004;Zawacki et al, 2003). Research with civilian samples has also shown an association between responses to measures of hostility toward women (e.g., "Sometimes women bother me by just being around") and sexual assault perpetration (Abbey and McAuslan, 2004;Hall et al, 2000).…”
Section: Sexual Assault Screening Toolsmentioning
confidence: 99%
“…Other factors that appear associated with sexual assault perpetration include alcohol use and drug use (Swartout and White, 2010;Zawacki et al, 2003). Various interpersonal-skill deficits have shown mixed associations with sexual assault proclivity (e.g., Baker and Beech, 2004;Fernandez and Marshall, 2003).…”
Section: Sexual Assault Screening Toolsmentioning
confidence: 99%
“…De plus, comparativement aux autres agresseurs sexuels et aux non-agresseurs, les hommes qui commettent une agression sexuelle en utilisant de l'alcool (consommé par la victime ou par eux-mêmes) rapportent avoir une consommation d'alcool plus élevée au moment où ils interprètent de façon erronée les intentions sexuelles de la femme. Ils croient aussi davantage que l'alcool améliore leur désir sexuel et que le fait que les femmes boivent de l'alcool signifi e également un intérêt sexuel de leur part (Zawacki, Abbey, Buck, McAuslan, et Clinton-Sherrod, 2003). D'autre part, dans une étude menée en laboratoire, George, Stoner, Norris, Lopez, et Lehman (2000) ont identifi é que, parmi les hommes qui ont des attentes sexuelles reliées à l'alcool, ceux qui croient en avoir consommé (alors que dans les faits ils ont consommé une boisson non alcoolisée) sont plus excités sexuellement par des images de coercition sexuelle, que ceux qui savent qu'ils ont bu une boisson sans alcool.…”
Section: Drogues Santé Et Société Vol 4 N Ounclassified